Islamic Education Methods For The Millennial Generation In The Perspective Of The Quran And Hadith - Jahroh, Fatimah (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Educational methods are fundamental for achieving learning outcomes, also for creating active and effective learning, and encouraging students so they can explore and develop their talents and abilities. Starting from intelligence, personality, morals, and skills that are beneficial for oneself and society. This research uses qualitative research methods through literature study with a descriptive-narrative approach and data collection techniques in the form of reading texts related to the required data. The collected data is classified into sub-discussions and analyzed using content analysis techniques, then arranged descriptively narratively into a systematic article. This research aims to describe what Islamic education methods are suitable for the millennial generation from the perspective of the Koran and Hadith. This article produces the result that Islamic education methods are still very valid and can be applied at all times to anyone and at any time by the Koran and hadith. The results of this research show that the Islamic education method is a method of regular and systematic education by what is taught in the Islamic religion which is based on the Koran and hadith. And this Islamic education method is also very suitable for millennial generation children, such as the exemplary method (al-uswah al-hasanah), the lecture method, the discussion/dialogue method, and the targhib and tarhib methods. Keywords: Islamic Education Methods, Millennial Generation, in the Perspective of the Alquran and Hadith